Teaching Effectiveness for Engineering Fourth Year Undergraduate Learning During School Restrictions - Suriati Akmal; Ruzy Haryati Hambali; Masni Azian Akiah (Universitas Merdeka Malang, 2021)
The school restrictions caused by pandemics have changed the teaching strategy. This study aims to examine the effectiveness of teaching strategies with the aids of a learning management system on student performance. A fourth-year course called Concurrent Engineering course of Faculty of Manufacturing Engineering at the Universiti Teknikal Malaysia Melaka was selected to demonstrate the merits of the strategies. The course was offered once per year which is only semester 2 every session. For this purpose, a set of the questionnaire was distributed to 33 students after the summative assessment. The teaching effectiveness was measured through course contents, knowledge, attitude, students’ satisfaction that adopted from existing literature. The results of the study were analyzed using descriptive analysis involving mean and standard deviation. Teachers’ attitude is the most influential factor for teaching effectiveness. The highest item in this factor is the teacher has created a teaching and learning environment that stimulates positive learning attitudes of students with a mean of 4.35 and standard deviation of 0.689. The impact of teaching effectiveness can be seen from the results of formative and summative assessments. The results show that the overall performance of students was good with 6.25% students attained grade A-. The performance is better in comparison to the previous session. And indicated that the new teaching strategy does not result in a decrease in student performance below what is normally achieved. The findings of this study show that technology is a must and must be parallel to teachers' attitude cannot be ignored to deliver effective teaching that can stimulate a positive learning environment.